FOREIGN EXPERIENCE OF LABOR INSPECTION ACTIVITIES - Bokovykova Yu.V. (Pressing Problems of Public Administration, 2017)
The article is devoted to the problems of state supervision and control over the compliance oflabour legislation in foreign countries. Considering the experience of other countries the ways tosolve problems in the sphere of supervision and control over the compliance of labour legislation areproposed.